Neonatal solid tumors - Aravindan Chandrasekaran (Elsevier, 2018)
Background: Neonatal tumors are different from tumors of the older children and knowledge gained from treating older children can not be extrapolated to neonates. Neonates have immature physiology and their haematopoietic and immune systems are not fully developed and the response to therapy is unpredictable. Hence it is imperative to study these tumors as separate entity.The aim of this study is to analyse this rare set of tumors in terms of their incidence, clinical features and management. Materials and methods: All babies admitted in our hospital with tumors from January, 2011 to January 2016 were studied. Tumor-like conditions like haemangioma, lymphangioma and hamartomas were included. The age, sex distribution, type of tumor and management were studied. Results: A total of 51 cases were registered out of which, 29 cases were haemangiomas and lymphangiomas. Of remaining 20 cases, 5 were benign ovarian cysts, 3 were neuroblastomas, 3 were congenital fibrosarcomas, 3 were sacrococcygeal teratomas. Wilm's tumor, congenital mesoblastic nephroma, haemangioendothelioma of liver and others formed the remaining six cases. Conclusion: Our study insists that the neonatal tumors are distinct subset of pediatric tumors, requiring careful selection of treatment modalities and most of the solid tumors can be successfully managed if diagnosed and treated early. Neonatal tumors are defined as tumors which are diagnosed before the first month of life. Some of them can be congenital (present at birth). Neonatal tumors are different from tumors in older children in terms of etiopathogenesis, behavior and response to therapy as well as long-term outcomes.